2015
DOI: 10.1177/0003489415575057
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum and Clinical Features of Patients With ACTG1 Mutations Identified by Massively Parallel DNA Sequencing

Abstract: Target exon-sequencing using MPS was proven to be a powerful new clinical diagnostic tool for the identification of rare causative genes such as ACTG1. The present clinical findings not only confirmed those previous reports but also provided important new clinical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
(65 reference statements)
1
27
0
Order By: Relevance
“…The rate of progression of hearing loss caused by EYA4 was considered to be 0.63 dB/year (95%CI: 0.41-0.85 dB/year). In previous reports on ADSNHL hearing loss, the progression rate for the POU4F3 gene was 0.5-0.9 dB/year 41 , that for MYO6 was 2.0 dB/year 45 , and that for ACTG1 was 2.0-6.0 dB/ year 46 , and the results in this study suggests that the rate of hearing loss progression caused by EYA4 may be relatively mild.…”
Section: Discussionsupporting
confidence: 68%
“…The rate of progression of hearing loss caused by EYA4 was considered to be 0.63 dB/year (95%CI: 0.41-0.85 dB/year). In previous reports on ADSNHL hearing loss, the progression rate for the POU4F3 gene was 0.5-0.9 dB/year 41 , that for MYO6 was 2.0 dB/year 45 , and that for ACTG1 was 2.0-6.0 dB/ year 46 , and the results in this study suggests that the rate of hearing loss progression caused by EYA4 may be relatively mild.…”
Section: Discussionsupporting
confidence: 68%
“…The 11 reported mutations in 17 individuals are distributed across all four subdomains [Holmes et al, ], and include three clusters of mutations: Met153‐Ser155 (N = 4), Arg254‐Arg256 (N = 5), and Glu334‐Arg335 (N = 2). We found no overlap between mutations associated with isolated hearing loss and BWCS (HGMD and ClinVar, accessed April 2016), although two mutations affect nearby residues: p.(Lys118Met) and p.(Lys118Asn) with isolated hearing loss, and p.(Thr120Ile) with BWCS [Miyagawa et al, ; Yuan et al, ]. However, craniofacial features of DFNA20/26 patients have been neither illustrated nor discussed in detail.…”
Section: Discussionmentioning
confidence: 92%
“…Since the expression of ACTG1 is located within the cochlea, comparatively good outcomes for CI/EAS can be expected. In fact, our studies demonstrated that EAS was an effective therapeutic intervention for patients with ACTG1 mutations (Miyagawa et al, , ).…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%
“…E : Hearing thresholds with EAS. F : Japanese monosyllable test results showing dramatic improvement with EAS (Miyagawa et al, ).…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%